Taṭwīr al-Tadrībāt al-Lughawiyyah al-‘Arabiyyah bi-Istikhḍām al-Al‘āb al-Tafā‘uliyyah Wordwall - Ummah, Khaira; S, Yelfi Dewi (al-Ittijah: Jurnal Keilmuan dan Kependidikan Bahasa Arab, 2025)
This Research and Development (R&D) study aims to innovate interactive Arabic language exercises through the Wordwall platform to address the limitations and monotony of traditional instructional methods at Jam'iyatul Hujjaj Primary School. The study adopted the ADDIE instructional design model, encompassing five systematic phases: Analysis, Design, Development, Implementation, and Evaluation. The research was conducted with a sample of 30 third-grade students, utilizing observation, interviews, questionnaires, and pre- and post-tests as primary data collection instruments. The results indicate that the developed exercises achieved high validity ratings (78%–80%) based on expert validation and demonstrated excellent practicality scores (90%–98%) among both students and the teacher. Furthermore, quantitative analysis confirmed the product's effectiveness in improving linguistic performance, as evidenced by an average N-Gain score of 0.83, which categorizes the intervention as "highly effective." These findings highlight the critical role of digital transformation in Arabic pedagogy to foster active engagement and bridge the gap between standardized curriculum content and modern learner needs. However, the study is limited by its small sample size and specific institutional context. Consequently, it is recommended that future research expand the experimental scope and explore the integration of Artificial Intelligence (AI) to develop adaptive learning systems for young Arabic language learners.